A Westend árnyékában (Szociológiai Szemle, 2024)
The study examines the subject of city rehabilitation by pulling down older buildings. The area designated to be demolished is an apartment block at the corner of Munkácsy Street and Podmanicky Street in District 6 in Budapest.The survey was conducted based on questionnaires and interviews with experts and non-experts. The researchers' main job was to collect information to help the municipalities in order to offer an acceptable substitute housing to the residents. They have included certain broader considerations and questions to this concrete goal.According to the results, the majority of the occupants agreed on the demolition of their house, mainly because of the physical condition of these houses. However, they did not wish to leave their familiar neighborhood. They wanted to remain in the district, in a similar location. The overall majority of those who live in the neighborhood agreed to the demolition, yet their opinion varied in respect of the eight buildings. Were the residents' choice decisive, the old MÁV-buildings on Podmanicky Street would remain intact. Nevertheless, this alternative cannot be considered as a valid choice because of the intent to sell the land in its entirety. The findings revealed a very strong social network in this apartment block. Were the occupants dispersed, this network would disappear; thus, the existing precious social bonds would be broken up. The "case" is not finalized, as the occupants have not moved yet. The researchers intend to follow the future of this community.